PENINGKATAN KINERJA PENGAWAS MELALUI LAYANAN PENGEMBANGAN PROFESI PENELITIAN TINDAKAN KOTA SAWAHLUNTO - Yusmaini Yusmaini (IAIN Batusangkar, 2016)
This research focused on the low of supervisor’s job performance in Sawahlunto based on the worse of planning and motivation. This case was from the lack of service on developing supervisor’s competence at ministry of religion Sawahlunto. This research was an action research where it aimed at testing hypothesis and upgrading supervisor’s job performance through improving service and professional development. The participant of this research was 7 supervisors at ministry of religion Sawahlunto. The data were collected by using interview and documentation. The findings revealed that the supervisor’s job performance on the cycle I was better with 75.29%. The cycle II, the supervisor’s job performance more better with 7,42%. Keywords: Job Performance, Service, Planning, Motivation.